Long-Term Mild Heat Causes Post-Mitotic Pollen Abortion Through a Local Effect on Flowers - Xu, Jiemeng; Jansma, Stuart Y.; Wolters-Arts, Mieke; de Groot, Peter F. M.; Jansen, Martijn J.; Rieu, Ivo (Frontiers in Plant Science, 2022)
Crop reproductive success is significantly challenged by heatwaves, which are increasing in frequency and severity globally. A major reason is reduced male fertility due to deviations in pollen development, but the mechanism behind this is not well understood. Here, long-term mild heat (LTMH) treatment, mimicking a heatwave, was applied locally to tomato flowers or to whole plants and followed up by cytological, transcriptomic and biochemical analyses. LTMH was shown to act directly on the flowers and not via a systemic effect on other plant tissue. The meiosis to early microspore stage was the most sensitive to LTMH and three days of exposure around this period was sufficient to significantly reduce pollen viability. Extensive cytological analysis showed that abnormalities in pollen development could first be observed after pollen mitosis I, while tapetum development appeared unaffected. Transcriptomic and biochemical analyses suggested that pollen development suffered from tapetal ER stress and that there was a limited role for oxidative stress. These characteristics differentiate the response of developing anthers and pollen to LTMH from the response to severe heat stress.